Answers

2014-08-17T17:22:31+08:00
0
the answer she is looking for is standard form, right? But that aswer is y-form
2014-08-17T17:30:00+08:00

all you need to follow is this formula: (y-y1)=m(x-x1)

your m will be -2/3 and your y1 will be 5 and your x1 is -3 so your solution is

(y-5)=-2/3(x+3)

after that distribute 3 to (y-5) and -2 to (x+3)

after distributing your answer will be 3y-15=-2x-6 after that transpose all

and that will be 2x+3y=-6+15 since its not yet done finish -6+15 that will be 9 so your standard form will be 2x+3y=9 

0